The new facet of smoking: the use of electronic cigarettes in the context of public health (Research, Society and Development, 2022)
Smoking was encouraged and seen as a symbol of beauty for a long time until its strong negative impact on human health was evidenced, unfortunately with the emergence of new smoking devices such as the electronic cigarette, what can be referred to as a new smoking mode. Thus, this article aims to highlight the use of electronic cigarettes and potential health causes, identifying the damage caused by electronic cigarettes to the user and consequently their impact on public health. This is a narrative review study of the literature, with a qualitative approach. The use of electronic devices becomes a possible perpetuator of the act of smoking and may represent initiation and even the permanence in smoking. There are already losses related to the use of electronic cigarettes (EC), they cause toxicity to the body, it can also cause dependence and cause diseases in the pulmonary, cardiovascular and gastrointestinal systems, causing imbalance in the human body, the use of EC is also related to problems in mental health such as irritation. It is clear that the use of electronic cigarettes promotes harm both to the user and to public health, requiring more and more rules to supervise the dissemination of advertisements and commercialization of the product. Thus, it is suggested that further research be carried out in order to corroborate evidence of the harm caused by the use of EC, in order to understand its different aspects and devise strategies to reduce its effects, aiming at improving the health of the entire community.